Pathogenic advances in rheumatoid arthritis: a review - Abdullah, Muhammad Nazrul Hakim; Md Tohid, Siti Farah; Keong, Yong Yoke; Nordin, Nurul Syuhada (Universiti Kuala Lumpur, 2024)
Rheumatoid arthritis (RA) affects approximately one percent of people worldwide. It falls within the category of an inflammatory immune-mediated illness where the primary tissue location is the joint. Environmental and genetic factors combine to cause RA. The exact onset of the disease is unknown, as is the appropriate time at which to diagnose it as RA. In RA, the synovial membrane and surrounding tissues are attacked by the immune system. The pathophysiology of RA still raises three unanswered problems. First, how the environment or heredity drives the immune system. Secondly, how it persisted in causing inflammation in the surrounding joint, and thirdly, how inflammation results in damage to bones. There are various number of cells associated in the progression of RA disease. Proinflammatory cytokines are mostly produced by macrophages, which can also serve as antigen-presenting cells. In joints, the fibroblast-like synoviocytes (FLS) interact with cells of the innate host immune system and activate B and T cells causing an increase in chemokines and cytokines production such as TNF-α, IL-1, and IL-6 thus allowing a feedback loop to occur. B cells, T cells, and macrophages will all play a part in these extra encounters. Matrix metalloproteinases (MMPs), prostaglandins (PGs), and inflammatory cytokines were also produced in varying quantities by the activated fibroblast-like synoviocytes within the synovial membrane. The accumulation of chemokines and nitric oxide (NO) also contributes to inflammation and tissue catabolism. MMPs enter the synovial fibroblast (SF) directly as a result of the positive feedback loop, which can lead to the degeneration of bone and cartilage. We herein summarized the key pathogenic advances informing these issues with the basics of rheumatoid arthritis and its mediators, together with the cell signalling pathways involved.